Preoperative Evaluation of Central Lymph Nodes in Papillary Thyroid Carcinoma Using High-Resolution Ultrasound and Shear-Wave Elastography. Issue 4 (December 2021) - Liu, Ying; Li, Sheng; Yun, Miao; Lin, Xi; Lin, Yidi; Long, Xingzhang; Zhou, Jianhua; Liu, Longzhong
Abstract : Abstract: The aim of this study was to discuss the diagnostic value of high-resolution ultrasound and virtual touch tissue imaging quantification (VTIQ) for distinguishing metastatic and benign central lymph nodes (CLNs) in patients with papillary thyroid carcinoma. This retrospective study involved 86 pathologically proven benign lymph nodes (LNs) and 118 metastatic LNs in patients with papillary thyroid carcinoma. We analyzed the sonographic features of CLNs (size, shape, distribution, hilum, echogenicity, cystic change, calcification, vascularity, shear-wave velocity [SWV]). The prevalence of sonographic features and the SWV was compared between metastatic and benign CLNs. The size, shape, margin, distribution, presence of hilum, echogenicity, calcification, and vascularity were significantly different between benign and metastatic CLNs ( P < 0.05 for all). The mean maximum SWV for malignant CLNs was 3.139 ± 0.408 m/s, whereas that of benign CLNs was 2.418 ± 0.369 m/s ( P < 0.05). The cutoff point of the SWV for differentiating benign and malignant LNs was 2.675 m/s. Logistic regression analysis showed that round or irregular shape, aggregation or fusion, calcification, and VTIQ value greater than 2.675 m/s of CLNs were independent risk factors for malignancy, with an odds ratio of 5.77, 3.05, 3.23, and 62.85, respectively. High-resolution ultrasound and VTIQ can provide valuable information for distinguishing metastatic from benign CLNs.